The Orient in music : music of the Orient - Grajter, Małgorzata (Cambridge Scholars Publishing, 2017)
""OM"", a fundamental meditation sound present in the cultures of Buddhism, is a syllable full of philosophical and transcendental meanings. The category of the Orient, as contrasted, antithetical and complementary to the Occident (West) and its culture, appears to be one of the most interesting and long-lasting issues discussed in the humanities. European fascination with Oriental cultures has found multifaceted manifestations in science, art, fashion and beliefs. Music, as an important element of cultural communication, has always been well suited for transitions and inspirations. The relatio